if f(x) = -5* - 4 and g(x) = -3x - 2 ,find (f + g)(x)
![if fx 5 4 and gx 3x 2 find f gx class=](https://us-static.z-dn.net/files/d5b/3d75b34c61234b264ab9f4e02e07dcd0.png)
By definition you know that
[tex](f+g)(x)=f(x)+g(x)[/tex]So, in this case, you have
[tex]\begin{gathered} f(x)=-5^x-4 \\ g(x)=-3x-2 \\ (f+g)(x)=f(x)+g(x) \\ (f+g)(x)=(-5^x-4)+(-3x-2) \\ \text{ Remove parentheses} \\ (f+g)(x)=-5^x-4-3x-2 \\ \text{ Add like terms} \\ (f+g)(x)=-5^x-3x-6 \end{gathered}[/tex]Therefore, the correct answer is B.
[tex](f+g)(x)=-5^x-3x-6[/tex]